MENINGKATKAN KOMPETENSI GURU PADA MASA PANDEMI COVID-19 MELALUI STRATEGI KEPALA SEKOLAH DI SMP NEGERI 45 MEDAN TAHUN AJARAN 2021/2022 - Sangkot Basuki (JGK (Jurnal Guru Kita), 2022)
Improving Teacher Competence During the Covid-19 Pandemic Through the Principal's Strategy at SMP Negeri 45 Medan for the 2021/2022 Academic Year. The purpose of school action research is to find out the principal's strategy in increasing teacher competency during the Covid-19 pandemic at SMP Negeri 45 Medan, Labuhan District. The research method is descriptive qualitative research, the subjects in this study were teachers at SMP Negeri 45 Medan, Labuhan District, the data collection techniques were: observation techniques, interview techniques and documentation studies. The results of this study are: 1) There are 3 strategies for increasing teacher competence during the pandemic. First, coaching teachers by learning to use Google Classroom during a pandemic. Second, directives, namely sending links to seminars, workshops, training and others so that teachers can follow them. Third, education and training, namely increasing the competence and professionalism and quality of teachers. 2) Supporting and inhibiting factors in increasing teacher competence during a pandemic are: supporting factors, a) Discipline, by arriving on time to school, b) Providing motivation, by giving advice during meetings and outside meetings to attract teachers' enthusiasm, c) Awards, in the form of opportunities to take part in competency improvement training and the awarding of certificates. The inhibiting factors are, a) The teacher's indifference to their performance, so that the teacher teaches subjects that are not in accordance with their qualifications, b) the lack of teachers mastering IT, so that the teacher has difficulty operating the technological media used in online training and online learning. It is recommended that teachers can further improve their competence by participating in competency improvement training and also increase their enthusiasm and enthusiasm to develop and improve their own competence.